Building Damage Assessment Using Remote Sensing Data and Deep Learning Algorithms - Sodeinde, Olalekan. (Tufts University. Tisch Library., 2024)
Thesis (Ph.D.)--Tufts University, 2023.; Submitted to the Dept. of Civil Engineering.; Advisor: Laurie Baise.; Committee: Laurie Baise, Babak Moaveni, Sumeeta Srinivasan, and Magaly Koch.; Keyword: Civil engineering.